CMOS transconductance multipliers: a tutorial - Gunhee Han; Sanchez-Sinencio, E. (IEEE transactions on circuits and systems. 2, Analog and digital signal processing, 1998)
Real time analog multiplication of two signals is one of the most important operations in analog signal processing. The multiplier is used not only as a computational building block but also as a programming element in systems such as filters, neural networks, and as mixers and modulators in a communication system. Although high performance bipolar junction transistor multipliers have been available for some time, the CMOS multiplier implementation is still a challenging subject especially for low-voltage and low-power circuit design. Despite the large number of papers proposing new CMOS multiplier structures, they can be roughly grouped into a few categories. This tutorial provides a complete survey of CMOS multipliers, presents a unified generation of multiplier architectures, and proposes the most recommended MOS multiplier structure. This tutorial could serve as a starting reference point (and metric) for comparison of new CMOS multiplier circuit configurations. An illustrative CMOS chip prototype verifying theoretical results is presented.